Інтродукція та селекція персика в ботанічному саду Дніпропетровського національного університету імені Олеся Гончара - Kabar, A.N.; Opanasenko, V.F.; Shoferistov, E.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
The results of peach interspecific hybrid forms introduction and selection in Botanical Garden of Oles Gonchar Dnipropetrovsk National University conditions are represented.